(untitled) (The International Journal for Scientific Research, 2025)
Agriculture is an important resource for Yemen and Yemenis, and coffee is at the forefront of cash crops and a source of income for more than 150,000 families, in recent decades its cultivation has declined due to the lack of water sources for irrigation, the scarcity of rainfall and the fluctuation of its seasons as a clear result of climate change. Selection and genetic improvement for the development of local varieties of coffee methodology can lead to reducing the effects of drought, so this research was carried out within an integrated methodology that begins to understand the mechanisms of adaptation and tolerance to drought, and then search for genetic variations that enable improvement and selection of adapted varieties and landraces. The study was conducted by tracking the growth of plants up to the age of one year and under adapted environmental conditions suitable for coffee as a plant and under four levels of water (80-60-20-40% of the field capacity). We evaluated traits related to vegetative growth, growth of the root system and physiological traits. The results showed that the coffee plant gradually declined its growth under the influence of the four levels of water quantity and the effect of drought was evident in some morphological characteristics such as the length of the plant and the number of leaves that remained alive, and the characteristics of the leaves were also affected in terms of their area and their dimensions also changed, as well as the characteristics of the dry weight of the leaves and the weight and length of the roots were important indicators that can be relied upon in the assessment of drought tolerance. The physiological characteristics also showed that the coffee plant shows adaptive mechanisms in increasing the chlorophyll content and increasing the density of stomata and the specific weight of the leaves, which allows plants to maintain the metabolism of the plant under drought conditions, which mechanisms can be used in the screening of local landraces of Yemeni coffee in the first stage. This laboratory study allowed researchers to develop a research protocol to assess the genetic variations of traits associated with tolerance or adaptation to drought, and can build on these results in understanding the mechanisms of tolerance of coffee plants to drought under Yemeni conditions.